Treatment-Emergent Neuroendocrine Prostate Cancer: A Clinicopathological and Immunohistochemical Analysis of 94 Cases - Zhang, Qingfu; Han, Yunan; Zhang, Yao; Liu, Dan; Ming, Jian; Huang, Bo; Qiu, Xueshan (Frontiers in Oncology, 2021)
Abstract PURPOSE: The aim of this study was to evaluate the pathological characteristics, immunophenotype, and prognosis of treatment-related neuroendocrine prostate cancer (T-NEPC). MATERIALS AND METHODS: 231 repeated biopsy specimens of castration-resistant prostate cancer (CRPC) cases were collceted between 2008 and 2019. Histopathological evaluation and immunohistochemical staining for Synaptophysin（SYN ), ChromograninA(CgA ), CD56, Androgen receptor (AR), and prostate specific antigen(PSA) to screen out T-NEPC cases. Multivariate analyses were performed to identify factors in the prognosis of T-NEPC. Further, The results were verified in SEER program. RESULTS: Among the 231 CRPC cases, 94 (40.7%) cases were T-NEPC. T-NEPC were more likely to negatively express of AR and PSA than CRPC. Kaplan-Meier analysis revealed that patients with T-NEPC(OS from T-NEPC diagnosis, median OS 17.6 months, 95% CI: 15.3-19.9 months) had a significantly worse survival compared with usual CRPC patients (OS from CRPC diagnosis, median OS 23.6 months, 95% CI: 21.3-25.9 months, log-rank P=0.001), especially in metastasis cases ( median OS 15.7 months, 95% CI: 13.3-18.0 months) and patients with small cell carcinoma component (median OS 9.7 months ,95% CI: 8.2-11.2 months). Prostate adenocarcinoma with diffuse NE differentiation(median OS 18.8 months ,95% CI: 15.3-22.3 months) had poor outcome than those with usual CRPC (P =0.027),while no significant change was observed in the focal neuroendocrine differentiation (median OS 22.9 months, 95% CI: 18.1-27.7 months, P=0.136). In unadjusted model, an excess risk of overall death was observed in T-NEPC with negative PSA (HR=2.86, 95% CI=1.39-6.73). In the 476 NEPC cases from SEER (2004-2017). An excess risk of overall death was observed in patients aged 65 years and older (HR=1.35, 95% CI=1.08-1.69), patients with PSA value ≤ 2.5 ng/ml (HR=1.90, 95%CI=1.44-2.52), patients with PSA value 2.6–4.0 ng/ml (HR=2.03, 95%CI=1.38-2.99), tumor stage IV (HR=2.13, 95%CI=1.47-3.08) and other races than white and black (HR=1.85, 95%CI=1.17-2.94) in pure NEPC. CONCLUSION: T-NEPC was associated with an unfavorable prognosis, negative expression of PSA in T-NEPC and serum PSA level ≤ 4 ng/ml had a worse prognosis. Urologists and pathologists should recognize the importance of the second biopsy in CRPC to avoid unnecessary diagnosis and treatment delays.